Design and Development of a Mobile Application for a Robotic Rehabilitation Process: DiagnoConn - Aktan, Mehmet Emin; Akdogan, Erhan (IEEE, 2017)
Over the last two decades, many academic studies have been published on the use of robotic technologies in physical therapy and rehabilitation. These studies have contributed in many ways to the rehabilitation process. Some of them are remote treatment, process monitoring and guidance. An effective communication between doctor, robot and patient are important things in the robotic rehabilitation. For this purpose, a SQL based mobile application called as DiagnoConn has been developed. This application allows communication between doctor, robot and patient. The system stores the treatment history of the patients and allows the doctors to access the all information of patients. The performance of the developed application was evaluated by the questionnaire. The overall satisfaction rate is 88%, indicating that user satisfaction is high enough.
Keywords: e-health; mobile application; rehabilitation robotics; diagnosis; Computer Science